Comparison of Types and Size of Biomass on Pirolysis Combustion Toward The Results of Bio-Charcoal and Liquid Smoke - Kemas Ridhuan; Dwi Irawan; Rahmady Setiawan (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Biomass is a renewable carbon source and can be processed into gas fuels, liquid and solid fuels. Biomass has several types with different grain sizes. Biomass can be converted to other forms of energy by combustion pyrolysis. Pyrolysis is the chemical decomposition of organic matter through a heating process at high temperatures with little or no oxygen. The results of the pyrolysis process in the form of bio-charcoal and liquid smoke. The purpose of this research was to determine the comparison of types and sizes of biomass in pyrolysis combustion with characteristics of bio-charcoal and liquid smoke. This research method uses rubber shell biomass waste, green coconut husk and rice husk. Biomass is burned by slow pyrolysis in the reactor with biomass fuel. Combustion in reactors and pitot tubes containing biomass. Measured temperature, time, amount of biomass, bio-charcoal and liquid smoke and the heating value of bio-charcoal. The research results obtained the heating value of rubber shell bio-charcoal at 6661.55 cal / gr, bio-charcoal yield of 2.3 kg, liquid smoke yield of 0.242 kg, green coconut husk biomass heating value amounted to 5388.56 cal/gr, the yield of 1.8 kg of bio-charcoal, the result of liquid smoke of 0.308 kg. and rice husk biomass obtained the heating value of 3626.48 cal/gr with a bio-charcoal yield of 1.3 kg resulting from liquid smoke of 0.284 kg. Keywords: Combustion, Pyrolysis, Liquid Smoke, Charcoal, Biomass